Management of Diabetic Foot Ulcer- A case study - Gouri Sakre; Suresh Kishanrao (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2021)
Diabetic Foot Ulcers (DFU) is a common complication among neglected management or long-term diabetes in developing countries like India for want of requisite services. DFU is estimated to be affecting approximately 15% of diabetic patients during their lifetime. Other complications of diabetes include Diabetic retinopathy and glaucoma affecting eyes, mouth problems like gingivitis and periodontitis, Alzheimer's disease affecting brain, diabetic retinopathy affecting hands and legs, Erectile Dysfunction (ED) among men, kidney failures. From the public health point of view, Diabetic Foot Ulceration is important as it is preventable. Globally recommended measures include good control of blood sugar, HbA1c, haemoglobin, blood pressure, and lipid levels that help to reduce amputations up to 80%. Diabetic foot ulcers are common on pressure points like heels, toes, and plantar surfaces.  We report a rare case here due to 2 reasons 1. An unusual site 2. DFU development within a short duration of 2 years after diagnosis. A young lady in her late 30's developed foot ulcer over left lower malleolus because of the pressure point due to the professional practice (tailor) of squatting on the floor to work within 2 years of diagnosis of diabetes. Started as bilateral pedal oedema, that progressed to inflammation and induration of tissues over left malleolus. In a week's time it increased and started oozing non-purulent exudate. An initial antibiotic therapy gave some relief but recurred with purulent discharge after 2 weeks of stopping antibiotic. A surgical debridement and approximation of the edges of the ulcer was done to facilitate the growth of the epithelium across the ulcer bed. The wound took over a week's antibiotic therapy after debridement and over 3 months of insulin therapy and regular wound dressing to heal fully.